Hubungan Status Imunologis dengan Stadium Klinis pada Pasien Human Immunodeficiency Virus (HIV) - Viyani, Rio S. A.; Kurniasari, Kurniasari (Medical Scope Journal, 2025)
Abstract: Human Immunodeficiency Virus (HIV) infection is still quite common in Indonesia. The clinical stage of HIV determines HIV prognosis. Opportunistic infections are one of the criteria for assessing the clinical stage of HIV. Level of CD4 influence the incidence of opportunistic infections. This study aimed to analyze the relationship between immunological status and HIV clinical stage. This was an descriptive and analytical study with a cross-sectional design using 73 medical records of HIV patients who sought treatment at one of the hospitals in Jakarta between January 2022 and May 2023. Data on sex, body mass index, CD4 levels, clinical stage, and opportunistic infections were collected from medical records. The sample selection technique was consecutive non-random sampling. HIV patients that received antiretroviral therapy (ARV) were included in this study. The chi-square test was used for analysis with a significance level of 5%. The results showed that the majority subjects were male (63.0%), underweight (49.3%), CD4 <200 cells/mm3 (46.6%), had opportunistic infection of pulmonary TB (23.3%), and clinical stage III (45.2%). The chi-square test obtained a p-value of <0.001 for the relation between CD4 level and clinical stage of HIV. In conclusion, immunological status based on CD4 levels can be one of the factors used to assess the severity of HIV disease clinically in patients receiving ARV therapy. Keywords: human immunodeficiency virus; CD4; clinical stage; opportunistic infection    Abstrak: Infeksi Human Immunodeficiency Virus (HIV) masih cukup banyak ditemukan di Indonesia. Prognosis HIV dipengaruhi oleh stadium klinis HIV. Infeksi oportunistik dinilai dalam penentuan stadium klinis HIV. Kejadian dan jenis infeksi oportunistik tergantung pada kadar CD4. Penelitian ini bertujuan menganalisis hubungan status imunologis dengan stadium klinis pada pasien HIV. Jenis penelitian ialah deskriptif analitik dengan desain potong lintang dengan menggunakan 73 rekam medis pasien HIV yang berobat di salah satu RSUD di Jakarta antara Januari 2022 - Mei 2023. Data berupa jenis kelamin, indeks masa tubuh, kadar CD4, stadium klinis dan jenis infeksi oportunistik dikumpulkan dari rekam medis. Tehnik pemilihan sampel adalah consecutive non-random sampling. Penelitian ini hanya mengikutsertakan rekam medis dari pasien yang mendapatkan terapi antiretroviral (ARV). Analisis statistik menggunakan uji chi-square dengan tingkat kemaknaan 0,05. Hasil penelitian mendapatkan mayoritas pasien HIV berjenis kelamin laki-laki (63,0%), memiliki IMT underweight (49,3%), CD4 <200 sel/mm3 (46,6%), infeksi oportunistik TB Paru (23,3%), dan berada pada stadium klinis III (45,2%). Analisis hubungan antara kadar CD4 dengan stadium klinis HIV memperoleh nilai p<0,001. Simpulan penelitian ini ialah status imunologis yang diukur berdasarkan kadar CD4 dapat menjadi salah satu faktor yang digunakan untuk menilai derajat beratnya penyakit HIV secara klinis pada pasien yang menerima terapi ARV. Kata kunci: human immunodeficiency virus; CD4; stadium klinis; infeksi oportunistik